Effects of post-exercise cold-water immersion on performance and perceptive outcomes of competitive adolescent swimmers - Batista, Natanael P. [UNESP]; de Carvalho, Flávia A. [UNESP]; Rodrigues, Caio R. D. [UNESP]; Micheletti, Jéssica K. [UNESP]; Machado, Aryane F. [UNESP]; Pastre, Carlos M. [UNESP] (Springer Nature, 2024)
Purpose: To evaluate the effects of repeated use of cold-water immersion (CWI) during a training week on performance and perceptive outcomes in competitive adolescent swimmers. Methods: This randomized-crossover study included 20 athletes, who received each intervention [CWI (14 ± 1 °C), thermoneutral water immersion (TWI) (27 ± 1 °C) as placebo, and passive recovery (PAS)] three times a week between the land-based resistance training and swim training. The interventions were performed in a randomized order with a 1-week wash-out period. We tested athletes before and after each intervention week regarding swim (100 m freestyle sprints) and functional performance (flexibility, upper and lower body power, and shoulder proprioception). We monitored athlete’s perceptions (well-being, heaviness, tiredness, discomfort and pain) during testing sessions using a 5-item questionnaire. Athlete preferences regarding the interventions were assessed at the end of the study. We used generalized linear mixed models and generalized estimating equations for continuous and categorical variables, respectively (intervention x time). Results: We found a time effect for swim performance (p =.01) in which, regardless the intervention, all athletes improved sprint time at post-intervention compared to baseline. There was an intervention effect for pain (p =.04) and tiredness (p =.04), but with no significant post-hoc comparisons. We found no significant effects for other outcomes. All athletes reported a preference for CWI or TWI in relation to PAS. Conclusion: The repeated use of CWI throughout a training week did not impact functional or swim performance outcomes of competitive adolescent swimmers. Perceptive outcomes were also similar across interventions; however, athletes indicated a preference for both CWI and TWI.
Keywords: Adolescent; Athletic performance; Cryotherapy; Recovery; Swimming